INTELECTUAL CAPITAL IN PUBLIC ZAKAH INSTITUTION ON ZAKAH MANAGEMENT - Ansoriyah, Faizatul; Haryanti, Rina Herlina; Sulistyo W, Wahyu Febriyanto; Permatasari, Dinar; Nugraheni, Jacika Pifi; Purwasih, Ratna Amy (Spirit Publik: Jurnal Administrasi Publik, 2015)
Indonesia is the biggest moslem country, it has chance to reduction poverty through zakah. One of the zakah intitution is BAZ (Public Zakah Intitution). The purpose in study is to know about intelectual capital in public zakah Institution. Intelectual capital is important in zakah management. It consist of human capital, structural capital and relational capital.Research methodology is empirically qualitative research. The result of this study show that intelectual capital is not maximized.  Although the level of employee education is high but still lower innovation and creativity still low. Bazda In Surakarta is the temporal institution in Ministry of Religion.  Keywords:Intellectual Capital, Pengelolaan Zakat